Screen Exposure, Circadian Rhythm, Sleep, Physical Activity, and Health Anxiety in University Students During Online Education - Sümeyye Akçay; Mehmet Burak Uyaroğlu; Gamze Koyutürk; Zuhal Kunduracilar; Emre Serdar Atalay; Burcu Akkurt (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This study aimed to examine the associations between screen exposure, sedentary behavior, circadian rhythm, sleep, physical activity, and health anxiety among university students during the online education period.Method: A total of 130 healthy university students participated. Data on socio-demographic characteristics, sleep onset latency, wake-up times, nighttime light exposure, and screen time were collected. Participants also completed the Morningness-Eveningness Questionnaire, the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), the International Physical Activity Questionnaire (IPAQ), and the Short Health Anxiety Inventory.Results: The sample included 101 females (78%) and 29 males (22%). Weak positive correlations were found between wake-up time and sleep onset latency, phone use and sleep duration, PSQI and several sleep parameters, ESS and phone use, and health anxiety with both PSQI and ESS. Weak negative correlations were observed between phone use and computer time, circadian rhythm and both sleep duration and phone use, and between circadian rhythm and PSQI and ESS. There was a moderate positive association observed between the ESS and PSQI scores.Conclusion: The findings suggest that lifestyle changes associated with online education may be linked to alterations in students’ circadian rhythm, sleep quality, and health anxiety. However, most associations were weak, indicating that these outcomes are likely influenced by multiple interacting factors.